2010
DOI: 10.3109/09637486.2010.533160
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid and amino acid compositions of selected wild-edible mushrooms consumed in Turkey

Abstract: The fatty acid and amino acid compositions of 11 mushroom species commonly consumed were collected from the East Black Sea region of Turkey and analyzed. All species were characterized by a high content of linoleic acid (C18:2n-6) and glutamic acid. The highest content of linoleic acid (78.0%) and glutamic acid (29.4 μg/mg dry weight [d.w.]) was found in Agaricus arvensis and the lowest in Cantharellus tubaeformis, 19.8% and 10.9 μg/mg d.w., respectively. The average content of amino acids for all species was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…Limited data on amino acid composition of mushroom protein suggest a higher nutritional value than in most plant proteins. Findings were bolstered by the results of Ayaz et al . in 11 wild species.…”
Section: Chemical Composition and Nutritional Valuementioning
confidence: 81%
See 2 more Smart Citations
“…Limited data on amino acid composition of mushroom protein suggest a higher nutritional value than in most plant proteins. Findings were bolstered by the results of Ayaz et al . in 11 wild species.…”
Section: Chemical Composition and Nutritional Valuementioning
confidence: 81%
“…Limited data on amino acid composition of mushroom protein 2 suggest a higher nutritional value than in most plant proteins. Findings were bolstered by the results of Ayaz et al 20 in 11 wild species. Ranges of 93.6-230 and 39.7-86.8 g kg −1 DM were reported for total amino acid and essential amino acid contents, respectively.…”
Section: Proteins and Amino Acidsmentioning
confidence: 85%
See 1 more Smart Citation
“…The lipidic fraction of C. tubaeformis is mainly composed of oleic acid (59.7%), linoleic acid (19.8%), palmitic acid (13%), and eicosatrienoic acid plus arachidonic acid (3.5%). Ayaz et al., (2011) reported that oleic acid (57.8%), was the most abundant in C. tubaeformis collected in Turkey, followed by linoleic acid (19,8%), and palmitic acid (15,2%), and stearic in lower amounts (6.19%). Other minor fatty acid derivatives are formed in the fruit bodies of Cantharellus sp .…”
Section: Resultsmentioning
confidence: 99%
“…In homeopathic practice use leaves, young branches, bark, rhizomes, flowers, and fruits of thorns. Water infusion from the flowers of the plant is an effective laxative, soothing the nervous system, a diaphoretic and diuretic (Ozcan et al, 2008). Bark, young branches, roots of thorns have a diaphoretic and anti-sporadic effect (Ahmad et al, 1998).…”
Section: Introductionmentioning
confidence: 99%